2019
DOI: 10.1136/tobaccocontrol-2018-054402
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial health warnings and wear-out effects: evidence from a web experiment in 10 European countries

Abstract: ObjectiveThis paper examines whether there are possible wear-out effects associated with repeated exposure to pictorial health warnings on tobacco products. Wear-out effects can be general, that is, people get used to the presence of pictorial warnings in general, or specific to the content of the warnings (ie, the images used). Distinguishing between these two types of wear-out is important for understanding how to maintain the effectiveness of health warnings over time.MethodsThis study used data from two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…GHWs are an important component of the suite of tobacco control policies [63][64][65]. Literature has identified that a significant wear out becomes present when GHW are left in market over sustained periods [36,66,67]. To contribute to the evidence base, this review aimed to systematically identify and synthesize evidence from longitudinal studies which tested different GHW formats and message frames to understand the effects on perceived risk of smoking and benefits of quitting and intentions to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…GHWs are an important component of the suite of tobacco control policies [63][64][65]. Literature has identified that a significant wear out becomes present when GHW are left in market over sustained periods [36,66,67]. To contribute to the evidence base, this review aimed to systematically identify and synthesize evidence from longitudinal studies which tested different GHW formats and message frames to understand the effects on perceived risk of smoking and benefits of quitting and intentions to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the combination of text and pictures is more alarming than just a text warning. 34 It is therefore recommended to promote the use of warning pictures instead of the traditional text warnings on cigarette packages.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of health warnings to remain relevant and continue to command attention is an important question in public health education. Woelbert and d'Hombres 1 conducted a large experimental study in 10 European countries that had implemented differing warning styles. They find that graphic and text combined have a maximum effect in reducing intentions to smoke, but that this was attenuated in countries that had already implemented this warning style.…”
Section: Richard O'connormentioning
confidence: 99%